An historical study of United States religious responses to the Vietnam War a matter of national morality - Nutt, Rick. (Lewiston : Edwin Mellen Press, 2012)
A historical analysis of the how various American religious groups responded to the Vietnam war, both in support and in opposition.
Introduction -- A "preservation and extension of freedom:" background of the Vietnam War and religious attitudes toward U.S. foreign policy -- "Let every person be subject to governing:" religious leaders and organizations supporting United States policy in Vietnam -- "One could regret the killing and insist that it should continue:" denominational support for the Vietnam War -- "Our action in Vietnam falls within international law and the laws of war:" just war defense of the United States in the Vietnam War and the embrace of exceptionalism -- "Some are guilty, all are responsible:" liberal ecumenical para-religious organizations assess the morality of the Vietnam War -- "The greatest purveyor of violence in the world today: my own government": other Christian and Jewish organizations and leaders respond to the morality of the Vietnam War -- "Moral outrage over this war is simply not an emotion shared by the Nixon majority:" issues confronted by para-religious organizations and individuals during the Vietnam War -- "Does our nation need restraining by other nations?:" denominations questioning the morality of the Vietnam War Old-line Protestant denominational statements up to the Tet Offensive -- "The profound moral dimensions of the war and the chasm this opened in U.S. public opinion:" opposing the war with moral arguments and a new understanding of exceptionalism -- "The American ghetto and the Hanoi operation were a single enterprise:" rejecting the belief in United States morality and exceptionalism -- Conclusion.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Vietnam War, 1961-1975 -- Religious aspects; Vietnam War, 1961-1975 -- United States; Vietnam War, 1961-1975 -- United States; Vietnam War, 1961- 1975 -- Religious aspects; Vietnam War, 1961- 1975.; History; HISTORY / Military / Vietnam War; Electronic books